The mysterious wall paintings of Teleilat Ghassul, Jordan : in context - Drabsch, Bernadette, (Monographs of the Sydney University Teleilat Ghassul Project ;, 2015)
This volume is primarily concerned with the re-analysis of the wall paintings from the Jordanian Chalcolithic period (ca. 4700-3700 BC) settlement site of Teleilat Ghassul, first excavated in 1929 by scholars from the Pontifical Biblical Institute Rome and latterly by Australians from the University of Sydney. The seven major paintings were re-analysed using a methodology based on contextualisation, digital reconstruction, experimental replication and subject analysis.